Developing a 7P Marketing Strategy for Nail Art Services: A Benchmarking Case Study in Surabaya, Indonesia - Celine Frans; Wendra Hartono (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to develop an adaptive marketing strategy for nail art micro, small, and medium enterprises (MSMEs) in Surabaya, Indonesia, by integrating the 7P marketing mix with a benchmarking approach. Methodology: The research employed a qualitative exploratory design using benchmarking as the main analytical approach, with data collected through in-depth interviews and observations of selected nail art studios using purposive sampling, and analysed through thematic coding techniques including open, axial, and selective coding. Results: The findings indicate that effective marketing strategies in nail art MSMEs depend on the integrated implementation of the 7P marketing mix rather than isolated application, with benchmarking enabling businesses to identify best practices and adapt to dynamic market conditions. Findings: Benchmarking functions as a continuous learning mechanism that strengthens innovation, digital engagement, service quality, and brand consistency when aligned with internal marketing practices. Novelty: This study proposes an adaptive marketing strategy framework that combines benchmarking with the 7P marketing mix, transforming a traditional marketing model into a dynamic and learning-oriented system for creative service MSMEs. Conclusion: The adaptive framework offers both theoretical and practical insights for enhancing competitiveness and long-term sustainability in trend-driven and highly competitive markets. Type of Paper: Qualitative research.